Survey of Ionospheric Pc3‐5 ULF Wave Signatures in SuperDARN High Time Resolution Data. Issue 5 (18th May 2018) - Shi, X.; Ruohoniemi, J. M.; Baker, J. B. H.; Lin, D.; Bland, E. C.; Hartinger, M. D.; Scales, W. A.
Abstract: Ionospheric signatures of ultralow frequency (ULF) wave in the Pc3‐5 band (1.7–40.0 mHz) were surveyed using ∼6‐s resolution data from Super Dual Auroral Radar Network (SuperDARN) radars in the Northern Hemisphere from 2010 to 2016. Numerical experiments were conducted to derive wave period‐dependent thresholds for automated detection of ULF waves using the Lomb‐Scargle periodogram technique. The spatial occurrence distribution, frequency characteristics, seasonal effects, solar wind condition, and geomagnetic activity level dependence have been studied. Pc5 wave events were found to dominate at high and polar latitudes with a most probable frequency of 2.08 ± 0.07 mHz, while Pc3‐4 waves were relatively more common at midlatitudes on the nightside with a most probable frequency of 11.39 ± 0.14 mHz. At high latitudes, the occurrence rate of Pc4‐5 waves maximizes in the dusk sector and during winter. These events tend to occur during low geomagnetic activity and northward interplanetary magnetic field. For the category of radially bounded but longitudinally extended Pc4 events in the duskside ionosphere, an internal driving source is suggested. At midlatitudes, the poloidal Pc3‐4 occurrence rate maximizes premidnight and during equinox. This tendency becomes more prominent with increasing auroral electrojet (AE) index and during southward interplanetary magnetic field, which suggests that many of these events are Pi2 and Pc3‐4 pulsations associated with magnetotail dynamics during active geomagnetic intervals. The overall occurrence rate of Pc3‐5 wave events is lowest in summer, which suggests that the ionospheric conductivity plays a role in controlling ULF wave occurrence. Key Points: Pc5 waves occur predominantly at high and polar latitudes with a most probable frequency of 2.08 plus‐minus 0.07 mHz, while Pc3‐4 waves are relatively more common at midlatitudes on the nightside with a most probable frequency of 11.39 plus‐minus 0.14 mHz At high latitudes, Pc4‐5 wave occurrence rate peaks in the duskside ionosphere and during winter At midlatitudes, Pc3‐4 wave occurrence rate peaks premidnight and during equinox